Small producer participation in export vegetable supply chains and household labour allocation in Tanzania: An age-disaggregated approach - Marwan Benali; Bernhard Brümmer; Victor Afari-Sefa (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
High-value agricultural supply chains have been playing an increasingly important role in developing countries and have had significant effects on the rural labour markets. This paper analyses the simultaneous effects of small producer participation in the latter on both household hired labour demand and off-farm labour supply, using an age-disaggregated approach. Failing to reject the separability hypothesis as well as the exogeneity of small producer participation in export supply chains, we apply lognormal double-hurdle models and find that participation in vegetable export supply chains in Tanzania affects positively a household's decision to hire labour from all age groups. We also find that it increases the unconditional overall level of hired labour demand, while the age-disaggregated analysis shows that these effects benefit mostly rural youth. However, no evidence of an effect on household off-farm labour supply is found.
Keywords: I31; J43; O12; Q12; 330; export supply chains; hired labour; off-farm labour; small producers; rural youth